Breastfeeding and Weaning of Children: Identifying the Practice-relevant Issues in an Urban Area of Bangladesh (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
The initial six months of exclusive breastfeeding, followed by appropriate complementary feeding, are critical for children's optimal growth and development. Since the 1980s, numerous organizations in Bangladesh have been promoting breast feeding, yet age-old practices have not changed significantly. Still, approximately half of children in Bangladesh are not breastfed exclusively for six months and do not receive adequate complementary food. This study sought to identify the barriers and facilitators to implementing proper Infant and Young Child Feeding (IYCF) practices. A cross-sectional descriptive study was conducted at the Department of Pediatrics at Bangabandhu Sheikh Mujib Medical College, Faridpur, from February to June 2021. This study included sixty-six mothers with infants aged six to twenty-four months. Face-to-face in-depth interviews were used to collect qualitative data regarding the barriers and facilitators. Transcripts of interviews were translated, transcribed, and examined to determine the primary factors. The most prevalent factor was a lack of knowledge and experience with breastfeeding and supplemental feeding. In addition, contradictory feeding information from various sources and a lack of social support for pregnant and childbearing mothers with limited decision-making capabilities were significant obstacles. In contrast, mothers who received guidance from healthcare professionals before and after delivery and who were educated and received family support were more likely to follow the recommended practice. Interventions should be prioritized to encourage mothers to take timely antenatal and post-natal care and nutritional counseling during their visits. Educating and empowering them with adequate support from the family and society is essential.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):70-75